2017
DOI: 10.1007/s12195-017-0515-6
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study of Interactions Between Two Bioactive Components from Zingiber cassumunar and 5-Lipoxygenase

Abstract: Introduction-Compound D and DMPBD are compounds extracted from Plai or Zingiber cassumunar Roxb., which have antiasthmatic properties. Thai herbal pharmacopoeia have indicated that approximate 50% of Thai prescriptions for asthma contain Plai. However, the inhibition mechanisms of these compounds are not clearly known. Methods-In this study, molecular docking and molecular dynamics (MD) simulations have been used to simulate complex systems and analyze molecular interactions between these compounds and protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…( E )-1-(3′,4′-Dimethoxyphenyl)buta-1,3-diene ( 1 ) and ( E )-4-(3′,4′-dimethoxyphenyl)but-3-en-1-ol ( 2 ) bound at the same catalytic site of its natural substrate (AA) on the 5-LO enzyme. The binding energy calculations of the 5-LO complex with 1 , 2 , and zileuton (anti-asthma agent) were −29.15, −26.83, and −29.40 kcal/mol, respectively, which supports the competition between the 1 and 2 substrate inhibitors, which was the same as zileuton [ 53 ]. Overall, these accumulated results indicated that the extracts and components of the Z. cassumunar possess potential value in the prevention and treatment of various diseases related to inflammation.…”
Section: Bioactivities Of Extracts and Compounds From Z Cassumunarmentioning
confidence: 82%
See 2 more Smart Citations
“…( E )-1-(3′,4′-Dimethoxyphenyl)buta-1,3-diene ( 1 ) and ( E )-4-(3′,4′-dimethoxyphenyl)but-3-en-1-ol ( 2 ) bound at the same catalytic site of its natural substrate (AA) on the 5-LO enzyme. The binding energy calculations of the 5-LO complex with 1 , 2 , and zileuton (anti-asthma agent) were −29.15, −26.83, and −29.40 kcal/mol, respectively, which supports the competition between the 1 and 2 substrate inhibitors, which was the same as zileuton [ 53 ]. Overall, these accumulated results indicated that the extracts and components of the Z. cassumunar possess potential value in the prevention and treatment of various diseases related to inflammation.…”
Section: Bioactivities Of Extracts and Compounds From Z Cassumunarmentioning
confidence: 82%
“…The extracts (100 mg/mL) and compound D (50 and 100 mg/mL) attenuated the PMA-induced MMP-9 gene and expression in NCI-H292 cells. Recently, the analysis of molecular interactions between two constituents of Z. cassumunar and a protein target, the 5-lipoxygenase (5-LO) enzyme, involved with asthma symptoms, were studied using molecular docking and molecular dynamics simulations [ 53 ]. ( E )-1-(3′,4′-Dimethoxyphenyl)buta-1,3-diene ( 1 ) and ( E )-4-(3′,4′-dimethoxyphenyl)but-3-en-1-ol ( 2 ) bound at the same catalytic site of its natural substrate (AA) on the 5-LO enzyme.…”
Section: Bioactivities Of Extracts and Compounds From Z Cassumunarmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Jitapunkul et al (2018) , herbal pharmacopoeia of Thailand showed that about 50% of Thai recipes for asthma disease contain bangle rhizome extract. ( Jitapunkul et al, 2018 ), likewise in Indonesia and Malaysia, a lot of people use it to treat asthma ( Iswantini et al, 2011 , Jantan et al, 2008 , Kaewchoothong, 2009 , Lim, 2016 ).…”
Section: Pharmacological Properties Of Bangle (Zingiber Montanum Jkömentioning
confidence: 99%
“…Still related to asthma, Jitapunkul et al (2018) conducted a study of compound D and DMPBD (( E )-1-(3,4-dimethoxyphenyl) butadiene), extracted from the rhizome bangle, by molecular docking and molecular dynamics (MD) simulations with simulate complex systems and analyze molecular interactions between these compounds and protein target, 5-lipoxygenase (5-LO) enzyme. The results of this study showed that Compound D and DMPBD molecules bind at the same binding site of its natural substrate (arachidonic acid) on 5-LO enzyme, which is similar to the binding of commercial asthma drug (Zileuton) ( Jitapunkul et al, 2018 ).…”
Section: Pharmacological Properties Of Bangle (Zingiber Montanum Jkömentioning
confidence: 99%